Proyecto: educación en línea - Ligia María Angulo-Hernández (Revista Electrónica Educare)
This is a presentation of a proposal for authentic application of the basic criteria and elements to create projects related to on line education in Centers of Superior Education. It provides a guide in a useful summary format, which explains the main aspects in the creation of the project from the planning stage to the final stage supervision. It is supported by a range of specialists who were involved in the process including experts in knowledge, graphic design, system programmers, and organizational leaders.